Asuhan Kebidanan Komprehensif pada Ny. N Umur 23 Tahun dengan Malposisi dan Obesitas di Wilayah Kerja Puskesmas Bumiayu Kabupaten Brebes Tahun 2023 - Selvia Apriliani1; Maryam Maryam; Nurhidayah Nurhidayah (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Anomalous positioning is an abnormal position of the fetal vertex (with the small fontanelle as a marker) relative to the maternal pelvis. Oblique malposition is a cause of maternal mortality rate (MMR) of 3-10%. Obesity in pregnancy is a condition characterized by an imbalance between body weight and height. According to WHO data, the prevalence of obesity in 2021 was 340 million, with data in Central Java province reaching 6.62%. In Brebes Regency, the figure was 20.51% (2019). In the Bumiayu Community Health Center, data on obesity in pregnant women reached 63 in 2022. This study aims to provide comprehensive midwifery care for pregnant women, childbirth, postpartum, newborns, and family planning for Mrs. N, 23, with malposition and obesity. This study used a qualitative descriptive method with a comprehensive case study approach. Based on the comprehensive midwifery care provided to Mrs. N, 23, with malposition and obesity, the pregnancy outcome was found to be grade I. Her gestational age was not commensurate with her gestational age. Delivery was performed by vaginal delivery. No problems were found during newborn care up to 28 days. No problems were found during the postpartum period. Mrs. N chose intrauterine contraception (IUD) during pregnancy, but her husband did not allow it due to religious reasons. Appropriate midwifery care during pregnancy, childbirth, newborn care, postpartum care, and family planning is crucial for the health of both mother and baby. This allows early detection of risk factors, preventing potential complications, and reducing maternal and infant mortality.